2001
DOI: 10.1053/ejvs.2001.1337
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Arterial Blood Reperfusion of Normothermic Kidney in Renal Artery and Abdominal Aorta Reconstructive Surgery

Abstract: the results of this study indicate that kidney short-term reperfusion may protect renal tissue from prolonged cross-clamping ischaemia (up to 100 min), also in patients considered at high risk for acute renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Moreover, in our studies, we included only patients without severe preoperative renal failure, which represents a known risk factor for renal postoperative renal complications. In a first pilot study in which we analyzed 47 consecutive patients undergoing EVAR with TRF, GFR impairment was documented at RPS in the 10.6% of cases [24], but there was no significant difference in postoperative GFR between IRF and TRF.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, in our studies, we included only patients without severe preoperative renal failure, which represents a known risk factor for renal postoperative renal complications. In a first pilot study in which we analyzed 47 consecutive patients undergoing EVAR with TRF, GFR impairment was documented at RPS in the 10.6% of cases [24], but there was no significant difference in postoperative GFR between IRF and TRF.…”
Section: Discussionmentioning
confidence: 97%
“…In these cases, a valid alternative consists in temporary renal reperfusion. In fact, in a previous study [24], we demonstrated that the temporary restoration of renal arterial inflow through a Pruitt-Inahara shunt for 3 min after 30 min of cross-clamping ischemia, protected from postoperative renal failure in juxtarenal aortic surgery, is also considered in patients at high risk for acute renal failure. Another important cause of ARF in aortic surgery is renal atheroembolism.…”
Section: Open Surgical Repairmentioning
confidence: 96%
See 1 more Smart Citation
“…Acute kidney injury occurring in association with perfusion disorder deriving from hemorrhagic shock and I/R in the surgical treatment of RAAA and intensive care follow-up is a significant clinical problem that can result in high mortality rates [6,10,22] . Deriu et al [22] reported that short-term reperfusion can protect the right and left renal arteries against acute kidney injury developing in association with abdominal aortic aneurysm [22] . Studies have also reported that abdominal aortic aneurysm can result in acute kidney injury by causing the production of free oxygen radicals [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Although some clinical studies tried to establish an effective local renoprotective management (bypass, shunt with blood, perfusion with cold lactated Ringer's solution, local cooling, etc.) (3)(4)(5)(6)(7)(8), there is still no widely accepted method for preventing renal failure. The idea of influencing ischemia reperfusion impact using cytoprotective agents is object of current investigations (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%